Introducing a Canadian book series for reluctant readers into the Latin American market: the case of Orca Soundings - Quintana, Eva Sofia
This report examines the Spanish translation of four recent titles in the series Orca Soundings, from Orca Book Publishers. It explores the specifics of working for a reluctant reader market. It also details the efforts made to distribute the series into the Latin American market. The five parts of this document provide a general overview of the Canadian company Orca Book Publishers, an analysis of the Spanish versions of four new titles of the Orca Soundings series, and information on the distribution work initiated with Latin American companies.